Earnings Management and Profitability Analysis of Public Company Listed at Indonesia Stock Exchange: Before and After Acquisition - Ramanda, Bimo; Yustisia, Natali; Riwayati, Hedwigis Esti; AR, Hikmah; Pramesworo, Ignatius Septo (Dinasti Publisher, 2025)
This study aims to analyze the effect of earnings management and profitability on companies conducting acquisitions on the Indonesia Stock Exchange in the period 2017-2023. The focus of this study is to compare the conditions of earnings management and several profitability ratios of companies, namely return on asset, return on equity, and net profit margin, before and after the company conducted an acquisition. The sample in this study was 31 companies obtained through purposive sampling and the method used a parametric inferential statistical approach using SPSS 26 software. The results of the analysis showed that there were no significant differences in earnings management, return on asset, return on equity, and net profit margin before and after the acquisition. This study provides insight into the absence of significant changes in the company's financial performance post-acquisition, although this study is limited to short-term impact analysis.